Comparison of different ultrasonic tip angulations on time required for cast post removal - da Galera, Eduardo Silva [UNESP]; Xavier, Ana Claudia Carvalho [UNESP]; Kamozaki, Maria Beatriz Beber [UNESP]; Gomes, Ana Paula Martins [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Pagani, Clóvis [UNESP] (Jaypee Brothers Medical Publishing, 2014)
Aim: The aim of this study was to design, develop and compare ultrasound tips with different angulations on time required for cast post removal. Materials and methods: To test and compare the ultrasonic tips developed, 36 metal patterns were fabricated from tin bars, on a mechanical precision lathe. Each metal pattern simulated an endodontically treated tooth, without coronal remaining, prepared to receive a cast post with 10 mm long. The cast posts were cemented with zinc phosphate cement. The metal patterns with their respective intraradicular posts cemented were stored at 37ºC, at relative humidity 100%, for a period of 48 hours. After this period, the specimens were randomly divided into three groups, and each group was submitted to the action of one of the ultrasonic tips (n = 12): G1—tip with 30º angulation; G2—tip with 45º angulation and G3—tip without angulation (straight tip). Each ultrasonic tip was used on the surfaces of the cast posts (mesial, distal, buccal, lingual and incisal) for 5 seconds, at maximum power, until the cast post removal using an ultrasound device (Jet Sonic, Satelec System, Gnatus, Ribeirão Preto, SP, Brazil). The time required for cast posts removal was recorded and the data statistically analyzed by the ANOVA and Tukey tests (p < 0.05). Results: The means of time evaluated for cast posts removal were G1: 59.25s; G2: 119.0s and G3: 48.4s. Group 2 presented the highest mean value in seconds, differing statistically from G1 and G3. No significant differences were observed between G1 and G3. Conclusion: It may be concluded that the ultrasonic tip angulation had a direct influence on the time required for cast posts removal by ultrasound. When the different ultrasonic tips were compared, the 30° angulation and the straight tips required a shorter ultrasonic vibration time. All cast posts luted with zinc phosphate were successfully removed in a relatively short time by the different ultrasonic tips analyzed.
Keywords: Dental materials; Post and core technique; Ultrasonics; Zinc phosphate cement